PENGEMBANGAN BUDAYA KERJA DAN IKLIM ORGANISASI UNTUK MENINGKATKAN KINERJA PEGAWAI DI RSUD PURI HUSADA TEMBILAHAN - jurnalmap map; Marlina ÔÇÄ; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to describe the influence of work culture and organizational climate on employee performance at RSUD Puri Husada Tembilahan. The study population included all employees of Puri Husada Tembilahan Regional Hospital totaling 218 people, taken as many as 141 employees. Data collection is done by questionnaire. Then the data were analyzed with multiple regression analysis techniques. The results showed that work culture and organizational climate partially had a significant effect on employee performance. Work Culture is the dominant variable affecting the performance of employees at RSUD Puri Husada Tembilahan. Simultaneously work culture and organizational climate significantly influence employee performance. Organizational goals will be easily achieved if the organization can develop a work culture and create a healthy organizational climate so as to improve employee performance.